Pomiar dokonań w ośrodkach odpowiedzialności za procesy - Szydełko, Łukasz (Performance measurement in process responsibility centres, 2008)
In this article the author presents the problems with the performance measurement in process responisbility centres. The main aspects are connected with building the process orientated company, quality fields of metrics and using AHP method to choose the best metrics for centres.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 427-434